2016
DOI: 10.13005/ojc/320171
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication A Composite Electrode Based on MWCNT/Zeolite for Potentiometric Determination of Chromium (III)

Abstract: A nanocomposite based on carbon paste electrode fabricated, by using zeolite as ion carrier .Functional multi-wall carbon nanotube was used for improvement of electrode response. The optimal composition of CPE was built from 65% graphite powder, 20 wt% paraffin oil, 5% ion carrier (zeolite), 10% MWCNTs. Electrode showed Nernstian response 19.88 (±0.2)mVdecade "1 in the measuring range 10 "7 -10 "2 mol L "1 and showed detection limit of 6.3×10 -7 M. The sensor was successfully used for potentiometric titration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…According to the literature, Multi-walled carbon nanotubes (MWCNTs) have shown an ability to efficiently remove various organic pollutants such as dioxins, polychlorinated dibenzo-furans and biphenyls from aqueous environments 5,6 . Nowadays, considerable efforts have been made to produce metal-carbon nanocomposite materials, not only because the carbonic compound improves the mechanical properties of the composites, but also because the produced composites possess the properties of individual components with a synergistic effect 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, Multi-walled carbon nanotubes (MWCNTs) have shown an ability to efficiently remove various organic pollutants such as dioxins, polychlorinated dibenzo-furans and biphenyls from aqueous environments 5,6 . Nowadays, considerable efforts have been made to produce metal-carbon nanocomposite materials, not only because the carbonic compound improves the mechanical properties of the composites, but also because the produced composites possess the properties of individual components with a synergistic effect 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several nanocomposite sensors have been developed for Cr(III) monitoring [ 30 , 134 , 135 , 136 ]. In fact, ZAHRA HEIDARI et al [ 134 ] reported a nanocomposite electrode based on MWCNT/Zeolite for Cr(III) sensing.…”
Section: Electrochemical Sensors and Biosensors For Trivalent Chromentioning
confidence: 99%
“…Several nanocomposite sensors have been developed for Cr(III) monitoring [ 30 , 134 , 135 , 136 ]. In fact, ZAHRA HEIDARI et al [ 134 ] reported a nanocomposite electrode based on MWCNT/Zeolite for Cr(III) sensing. Zeolite was used as a selective ionophore and MWCNTs for their attractive chemical and physical properties such as high chemical stability, good conductivity, good mechanical strength and maximum specific surface area [ 2 ].…”
Section: Electrochemical Sensors and Biosensors For Trivalent Chromentioning
confidence: 99%
“…Recently ionselective electrodes proved promising alternative as these provide linear dynamic range, fast response time, non-destructive analysis and online analysis. To develop a good sensitive sensor for chromium ion determination [17][18][19][20][21][22][23][24], many efforts were done using various neutral ionophores. However, reported sensors showed narrow working concentration range, non-Nernstian response and high response time [25][26][27][28] and significant interference from foreign ions Egyptian Journal of Chemistry http://ejchem.journals.ekb.eg/ ________________________________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%